Influence of structural state of SiO2 minerals on aggregate reactivity / SiO2 mineralų struktūrinęs būsenos įtaka užpildų reaktyvumui - Gumuliauskas, Algirdas; Navickas, Artūras; Štuopys, Arminas (Journal of Civil Engineering and Management, 1996)
Interaction of an alkaline medium with a reactive aggregate determines not only characteristics of a liquid medium but also the aggregate reactivity, which depends mostly on rock composition. Reactive Lithuanian aggregates are from quartz minerals of cryptocrys-talline structure (chert and flint, Fig. 1 rocks) and from low temperature cristobalite with adsorption water (gaize rocks, Fig. 4). Reactivity of SiO2 minerals (rocks) was estimated by their origin, chemical-mineralogical composition, crystallinity index (Fig. 2), solubility in an alkaline solution. Shortcomings of these methods were caused by the aggregate policrystallinity (Fig. 5) and/or inidentity of the investigation conditions to real ones. An integrated method of promotion of the alkaliaggregate reaction with a following sieve analysis was proposed (Fig. 6 and 7). A real granulometrical and chemical- mineralogical composition of the aggregates was estimated by this method. The method was tested with flint, gaize or quartz sand aggregates in a fine-graded aggregate concrete (Fig. 8) with an alkaline medium (1N NaOH). The expansion of a concrete with the gaize aggregates was 1.0–1,5 times larger than with the flint. The expansion of a concrete with the quartz aggregates was insignificant. Concrete expansion with the same size and amount of the reactive rock grains and under favourable conditions to the alkaliaggregate reaction (other conditions were uniform) was greater with more reactive aggregates. Article in Lithuanian. First Published Online: 26 Jul 2012